MANAJEMEN PEMBENTUKAN KARAKTER MODERASI BERAGAMA DI SMP NEGERI 1 PERCUT SEI TUAN - Lbs, Erfiani; Siahaan, Amiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fostering religious moderation character among students plays a crucial role in cultivating tolerance, respect for diversity, and a harmonious atmosphere within the school environment. However, the implementation of religious moderation values has not been fully integrated into school management practices. This study aims to examine the management of religious moderation character building at SMP Negeri 1 Percut Sei Tuan, encompassing the stages of planning, implementation, as well as monitoring and evaluation. This research employs a qualitative approach with a descriptive design. Data were collected through interviews, observation, and documentation, involving the principal, vice principal, teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. This study is expected to provide a comprehensive depiction of the management of religious moderation character formation through school programs, school culture, and religious activities. The findings of this research are expected to contribute to the development of educational management in strengthening students' religious moderation character, as well as to serve as a reference for schools in developing effective and sustainable character education programs